Opportunities and challenges in processing and fabrication of ultra high temperature ceramics for hypersonic space vehicles: a case study with ZrB2–SiC. (17th October 2018) - Mukherjee, Ragini; Basu, Bikramjit
ABSTRACT: Among ultra high temperature ceramics (UHTCs), ZrB2 -based ceramics have received the most attention for applications in hypersonic space vehicles. However, UHTCs encounter several challenges pertaining to their processing to achieve the desired properties in order to optimally exploit their potential. In this perspective, the present work illustrates some of the sintering related challenges using a case study of ZrB2 –SiC based ceramics. Multi stage spark plasma sintering is carried out on ZrB2 –SiC based ceramics at 1500°C with metallic Titanium as sinter-aid. High hardness of up to 28 GPa is obtained in dense ceramics with finer microstructure. Furthering towards design and fabrication of real scale hypersonic application such as thermal protection system, efforts have been taken to prove the scalability of the ceramics by consolidating up to ϕ100 mm ceramic discs.